‘Ulamā’, Authority, and Political Relations: How the PCNU Jember Fatwā Influenced Public Policy on Gold Mining in Silo? - Mun'im, Zainul; Rahmad Harahap, Wahfiuddin; Putra, Rona; Santoso, Budhi; Viegri, Muhammad (Institut Agama Islam Negeri (IAIN) Pontianak, 2025)
Fatwās (Islamic legal opinions) are often perceived as having limited influence on public policy, particularly in environmental and mining-related issues. Existing research suggests that despite opposition from ‘ulamā’ (Islamic scholars) and local communities, mining operations often persist due to strong political and economic backing. However, the fatwā issued by the Jember Branch Board of Nahdlatul Ulama (PCNU Jember)—which declared gold mining in Blok Silo impermissible (ḥarām)—produced a notably different outcome. This fatwā not only successfully halted mining activities but also played a decisive role in the revocation of government-issued mining permits. This study aims to analyze the mechanisms through which the PCNU Jember fatwā influenced public policy in the gold mining conflict in Blok Silo. Employing a socio-legal approach and qualitative methods, the research incorporates in-depth interviews with five key informants, including PCNU Jember officials and local community leaders, alongside document and media analysis from relevant sources. Drawing on Pierre Bourdieu’s theories of field and capital, this study argues that the effectiveness of the PCNU Jember fatwā was not solely rooted in its fiqh-based (Islamic jurisprudence) arguments but was reinforced by the symbolic and social capital held by NU scholars. The strong religious authority of ‘ulamā’ within Silo’s social structure, combined with PCNU Jember’s political connections with the local government, played a crucial role in ensuring the fatwā’s policy impact. This article argues that religious fatwās can function as potent instruments of environmental advocacy, particularly in societies where ‘ulamā’ continue to exert significant influence over political and social spheres. [Fatwa keagamaan sering kali dianggap tidak memiliki pengaruh signifikan dalam kebijakan publik, terutama dalam isu lingkungan dan pertambangan. Studi-studi terdahulu menunjukkan bahwa meskipun terdapat perlawanan dari ulama dan masyarakat, aktivitas pertambangan tetap berlangsung karena kuatnya dukungan politik dan ekonomi. Namun, fatwa Pengurus Cabang Nahdlatul Ulama (PCNU) Jember tentang keharaman pertambangan emas di Blok Silo menunjukkan hasil yang berbeda. Fatwa ini tidak hanya berhasil menghentikan aktivitas pertambangan, tetapi juga mendorong pencabutan izin usaha pertambangan yang telah dikeluarkan oleh pemerintah. Artikel ini bertujuan untuk menganalisis bagaimana fatwa PCNU Jember dapat memengaruhi kebijakan publik dalam konflik pertambangan emas di Blok Silo. Penelitian ini menggunakan pendekatan sosio-legal dengan metode kualitatif, yang melibatkan wawancara mendalam dengan lima informan, termasuk pengurus PCNU Jember dan tokoh masyarakat setempat, serta analisis dokumen dan berita dari sumber-sumber yang relevan. Dengan menggunakan teori field and capital dari Pierre Bourdieu, artikel ini menemukan bahwa keberhasilan fatwa PCNU Jember tidak hanya bertumpu pada argumentasi fikih dalam teks fatwa, tetapi juga pada modal simbolik dan sosial yang dimiliki oleh ulama NU. Otoritas keagamaan ulama yang tinggi dalam struktur sosial masyarakat Silo, serta hubungan politik PCNU Jember dengan pemerintah daerah, menjadi faktor utama yang memungkinkan fatwa tersebut berpengaruh terhadap kebijakan publik. Artikel ini berargumentasi bahwa fatwa keagamaan dapat berfungsi sebagai instrumen advokasi lingkungan yang efektif, terutama dalam masyarakat yang masih menjunjung tinggi otoritas ulama.]